Trust and distrust of tsunami vertical evacuation buildings: Extending protection motivation theory to examine choices under social influence. (September 2017) - McCaughey, Jamie W.; Mundir, Ibnu; Daly, Patrick; Mahdi, Saiful; Patt, Anthony
Abstract: Tsunami vertical evacuation (TVE) buildings have the potential to save many lives. Yet whether TVE buildings actually save lives depends critically on whether people trust and evacuate to them, a question that has not previously been researched. We examine the case of the city of Banda Aceh, Indonesia, where a M8.6 earthquake on 11-April-2012 caused a spontaneous mass evacuation but no tsunami. Our survey of residents living near TVE buildings (n = 202) shows that they clearly prefer horizontal evacuation: in the 2012 earthquake, only 26% evacuated to a TVE building, while 74% evacuated horizontally; if a similar earthquake happened in the future, only 32% intend to evacuate to a TVE building, while 68% intend to evacuate horizontally. To investigate the reasons for this, we extend protection motivation theory to examine people's choices among protective actions under social influence. Those who prefer to evacuate horizontally do not trust the safety of the TVE building and think they can reach a safe inland destination in time, while those who prefer to evacuate to a TVE building think they cannot reach a safe inland destination in time. Encouragement from friends and family influences people's evacuation destinations but official information and training do not. These findings suggest that more attention to the social context is crucial for the effectiveness of TVE buildings. Our extension of protection motivation theory to include choices among protective actions under social influence can be broadly useful in research on self-protective behavior in natural hazards, public health, and other contexts.